Circ-METTL15 contributes to the proliferation, metastasis, immune escape and restrains apoptosis in lung cancer by regulating miR-1299/PDL1 axis - Rui Zhang; Liang Shang; Jinniang Nan; Kai Niu; Jixin Dai; Xintian Jin; Xianghua Zhang (Taylor & Francis Group, 2022)
Background Circular RNAs (circRNAs) are important regulators in the pathogenesis of lung cancer. The study aims to explore the function and mechanism of circRNA methyltransferase-like 15 (circ-METTL15) in lung cancer development. Methods The expression of circ-METTL15, miR-1299 and programmed death-ligand 1 (PDL1) were investigated by qRT-PCR assay. Cell viability, colony formation, cell proliferation and invasion were determined by MTT, colony formation, EDU incorporation and transwell assays, respectively. Cell apoptosis was attested by flow cytometry and TUNEL assays. Interferon-γ (IFN-γ) and Tumour Necrosis Factor-α (TNF-α) production were tested by enzyme-linked immunosorbent assay (ELISA), and the survival rate of cancer cells was assessed by cytotoxicity analysis. The protein expression was examined by western blot or immunohistochemistry (IHC) assay. The interaction between miR-1299 and circ-METTL15 or PDL1 was confirmed via dual-luciferase reporter assay. Xenograft models were established in mice to explore the role of circ-METTL15 in tumour growth in vivo. Results Circ-METTL15 was upregulated in lung cancer tissues and cells. Circ-METTL15 silencing suppressed cell proliferation, colony formation, invasion, immune escape and promoted cell apoptosis in lung cancer cells. Circ-METTL15 was a sponge of miR-1299, and it could exert regulatory function in lung cancer via miR-1299. Furthermore, PDL1 was a functional target of miR-1299, and miR-1299 inhibited lung cancer cell development via decreasing PDL1 expression. Moreover, circ-METTL15 controlled PDL1 expression by acting as a sponge of miR-1299. Besides, circ-METTL15 downregulation blocked lung cancer tumour growth in vivo by regulating the miR-1299/PDL1 axis. Conclusion Circ-METTL15 promoted lung cancer malignant progression at least partly through modulating PDL1 by sponging miR-1299.